More complex than expected—mapping activities and youths’ experiences at BioBlitz events to the rosette model of science communication - Lorke, Julia; Ballard, Heidi L.; Robinson, Lucy D. (Frontiers in Environmental Science, 2024)
Deficit, dialogue, or participation - which of these three main models of science communications is the best fit to describe activities and experiences of citizen science? One might assume that participation is the best match, but the reality of citizen science events is more complex. The rosette model of science communication offers a more detailed set of subcategories, e.g., educate, entertain, or do, in addition to the three main models - deficit, dialogue and participation (Metcalfe, 2019; Figure 1). To systematically describe citizen science activities and experiences, we apply data on what activities are offered and what young people (5-19 years old) experience when participating in a citizen science event format called BioBlitzes across the rosette model. The mapping results illustrate how the rosette model can help to make citizen science project designers and practitioners more aware of the various modes of science communications that they may encounter at BioBlitz events and increase the understanding of how design decisions about settings can shape participants’ experiences.